Education for sustainable development as diffusion of innovation of secondary school students - Prabawani, Bulan; Hadi, Purwanto; Zen, Irina Safitri; Afrizal, Teuku; Purbawati, Dinalestari (Sciendo, 2020)
Education for sustainable development (ESD) is essential to study in order to understand environmental changes from the perspective of student character building. This concept is the main foundation that refers to individual personality as a medium to build excellent capacity from an early age. At adolescent age, children experience a period with high emotional growth that encourages changes in attitudes and behavior patterns towards the surrounding environment. This exploratory study aimed at describing the relationship between environmental knowledge and students' attitudes and behaviors, along with challenging factors as the moderating variable, involving 320 participants from two junior high schools in two cities in Central Java, Indonesia. The data were analyzed using partial least square Smartpls v3.0. This study found that junior high school students had low environmental and social knowledge, but there was a good attitude and behavior tendency concerning the environment. The students' knowledge significantly influenced environmentally-friendly attitudes and behaviors, especially the social environment that the obstacles also became a significant moderating variable. Thus, schools and related parties should develop programs to increase the studentsí study orientation towards the environment and to have a collective awareness of the environment, specifically the ability to analyze and synthesize the surroundings.